2016
DOI: 10.1016/j.ajpath.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characterization of the Cellular and Molecular Contributors to Liver Fibrosis in a Murine Hepatotoxic-Injury Model

Abstract: The interplay between the inflammatory infiltrate and tissue resident cell populations invokes fibrogenesis. However, the temporal and mechanistic contributions of these cells to fibrosis are obscure. To address this issue, liver inflammation, ductular reaction (DR), and fibrosis were induced in C57BL/6 mice by thioacetamide administration for up to 12 weeks. Thioacetamide treatment induced two phases of liver fibrosis. A rapid pericentral inflammatory infiltrate enriched in F4/80(+) monocytes co-localized wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 46 publications
4
50
0
Order By: Relevance
“…In models of chronic CCl 4 ‐induced liver fibrosis, Ly6C lo monocyte‐derived macrophages were found to be critical for tissue repair, with persisting fibrosis associated with decreased levels of Ly6C lo monocyte‐derived macrophages 37 , 94 . In contrast, a recent study from MacDonald and colleagues 40 using a thioacetamide‐induced chronic fibrosis model showed that blockade of macrophage colony‐stimulating factor receptor (CSF1R, also known as CD115), the receptor for CSF‐1, resulted in decreased Ly6C lo monocyte‐derived macrophages in parallel with decreased fibrosis, suggesting that Ly6C lo monocyte‐derived macrophages are critical for driving fibrosis. Blockade of CSF1R, however, also results in the depletion of resident KCs, and hence the effects of depleted KCs would need to be disentangled before firm conclusions about the causation of reduced fibrosis can be gleaned from this model.…”
Section: Monocytes As Drivers Of Fibrosis or Resolution Of Fibrosis?mentioning
confidence: 91%
See 3 more Smart Citations
“…In models of chronic CCl 4 ‐induced liver fibrosis, Ly6C lo monocyte‐derived macrophages were found to be critical for tissue repair, with persisting fibrosis associated with decreased levels of Ly6C lo monocyte‐derived macrophages 37 , 94 . In contrast, a recent study from MacDonald and colleagues 40 using a thioacetamide‐induced chronic fibrosis model showed that blockade of macrophage colony‐stimulating factor receptor (CSF1R, also known as CD115), the receptor for CSF‐1, resulted in decreased Ly6C lo monocyte‐derived macrophages in parallel with decreased fibrosis, suggesting that Ly6C lo monocyte‐derived macrophages are critical for driving fibrosis. Blockade of CSF1R, however, also results in the depletion of resident KCs, and hence the effects of depleted KCs would need to be disentangled before firm conclusions about the causation of reduced fibrosis can be gleaned from this model.…”
Section: Monocytes As Drivers Of Fibrosis or Resolution Of Fibrosis?mentioning
confidence: 91%
“…99 In a mouse model, CSF-1 treatment promoted a limited amount of differentiation of infiltrating F4/80 lo CD11b hi monocytes into F4/80 hi CD11b lo resident macrophages, suggesting that CSF-1/CSF1R may be important in controlling differentiation of monocytes in the liver. 100 In addition, Melino et al 40 show that CSF1R blockade reduced injury in a mouse model of chronic fibrosis in parallel with a reduction in the numbers of Ly6C lo blood monocytes and monocyte-derived macrophages. Finally, the transcription factor Nur77 is critical for the development of Ly6C lo monocytes in the bone marrow and lack of Nur77 results in monocytes with a more proinflammatory phenotype, suggesting that Nur77 may also be important in controlling the phenotypic switch in tissues.…”
Section: What Factors Drive the Ly6c Hi To Ly6c Lo Phenotypic Transitmentioning
confidence: 99%
See 2 more Smart Citations
“…They could aggravate liver injury and create a blockade of inflammatory Ly‐6C + IM recruitment using the CCL2‐inhibitor, which might promote HF resolution by inhibiting pro‐inflammatory cytokine production. Furthermore, early recruitment of granulin‐secreting inflammatory monocytes to the liver resulted in a fibrotic microenvironment and promoted pancreatic cancer metastasis 16 . HSC‐derived signaling molecules promote differentiation of liver macrophages with both pro‐inflammatory and pro‐fibrotic functions mediated by IL‐6 and TGF‐β.…”
Section: Hepatic Fibrosismentioning
confidence: 99%